Analysis of Factors that Influence Investment Decisions with Financial Literacy as a Moderating Variable - Tia Mahrurotul Fikriyah; Dwi Suhartini (PT FORMOSA CENDEKIA GLOBAL, 2023)
Investment is an important driving factor in a country's economic growth. However, in making investment decisions, factors such as fundamental analysis, technical analysis, psychological factors, and financial literacy can influence the results of investment decisions. Therefore, this study aims to analyze these factors and their relationship with investment decisions. This study uses a quantitative method with a descriptive approach. The research subjects were students of the East Java